PEMBERDAYAAN LITERASI KEUANGAN MASYARAKAT DI DESA SINDANGKASIH KECAMATAN RANOMETO BARAT KABUPATEN KONAWE SELATAN - Millia, Heppi; Rostin, Rostin; Rahim, Manat; Arifuddin, Arifuddin; Balaka, Muh.Yani; Gamsir, Gamsir (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This service aims to socialize and educate the people of Sindangkasih Village about financial literacy in order to support the national program initiated by the Financial Services Authority and Bank Indonesia. Previous studies have shown that the financial literacy of Indonesian people in rural areas is still low. Meanwhile, advances in information technology and financial inclusion are growing rapidly. Financial difficulties are not only caused by low income, but also by factors of efficiency and effectiveness of its management. Not to mention the misuse of technological advances by certain parties that can harm the community financially. For this reason, this program is very urgent to be implemented so that the community can maximize access to financial inclusion with minimal risk. The methods used are lectures and discussions with program participants as feedback to evaluate the success of the service. The conclusion of the implementation of this program; Has succeeded in increasing the financial literacy of participants which is expected to be passed on to their colleagues and colleagues, although for participants with low education, more detailed guidance is needed.